Time-dependent morphological alterations of cold-stored small bowel in Euro-Collins and Ringer's lactate solutions - ERCAN, FERİHA (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2004)
Small bowel is one of the organs that can in principle be transplanted. Optimum preservation of the organ is essential for the success of transplantation. The aim of the present study is the investigation of time-related morphological changes of rat small, bowel. during preservation in hypothermic Euro-Collins (EC) and Ringer's lactate (RL) solution using light microscopy and transmission electron microscopy to evaluate the integrity of intercellular complexes of mucosal. epithelium, one of the tissues of the intestine that is most susceptible to ischemia. Small. bowels were perfused with either EC, RL solution or physiological saline solution and were placed in the different preservation solutions at 4degreesC for 0, 3, 6 and 12 h. The results of our study suggest that both preservation solutions are suitable for short-term preservation of the small bowel although RL solution is more effective than EC solution. However, we conclude that further improvement of preservation solutions and/or techniques are needed to perform long-term preservation. (C) 2004 Elsevier GmbH. All rights reserved.
Keywords: preservation solutions; Euro-Collins solution; Ringer's lactate solution; transmission electron microscope; small bowel; UNIVERSITY-OF-WISCONSIN; RAT SMALL-BOWEL; CANINE SMALL-BOWEL; INTESTINAL TRANSPLANTATION; GRAFT VIABILITY; STORAGE METHOD; TISSUE-INJURY; PRESERVATION; ISCHEMIA; REPERFUSION